(untitled) (Prosiding Keislaman dan Sains, 2025)
This study aims to determine whether there is a relationship between self-acceptance and social anxiety in juvenile prisoners. The hypothesis in this study is that there is a negative relationship between self-acceptance and social anxiety in juvenile inmates at the Pekanbaru Special Prison for Children. The sample in this study amounted to 85 child prisoners at LPKA Pekanbaru with an age range of 14-18 years taken using total sampling technique. This study uses two psychological scales, namely the self-acceptance scale and the social anxiety scale. Data analysis in this study used person product moment correlation technique. This study produced a correlation coefficient of r = -0. 232 with a significance value of p = 0.032 <0.05 which means the hypothesis is accepted. The results of data analysis show that there is a negative relationship between self-acceptance and social anxiety in juvenile prisoners at LPKA Pekanbaru. This means that the higher the self-acceptance of child prisoners, the lower the social anxiety, on the contrary, the lower the self-acceptance of child prisoners, the higher the anxiety in child prisoners